Constituintes químicos de Tabebuia Impetiginosa (Mart) Standl. Bibnoniaceae - Ferreira, Dalva Trevisan; Oliveira, Alaíde Braga de; Castro, Clarice Ribeiro de (Semina: Ciências Exatas e Tecnológicas, 2004)
Ethyl acetate extract of the wood of Tabebuia impetiginosa afforded lapachol, dehydro -a- lapachone, lapachenol, vanillic acid and sitosterol.